Pengaruh Investasi, Inflasi, Kemiskinan, dan Ekspor Terhadap Pertumbuhan Ekonomi Indonesia - Susanti Nasution; Ansofino Ansofino; Jolianis Jolianis (Lembaga Teewan Journal Solutions, 2026)
This study analyzes the influence of investment, inflation, poverty, and exports on economic growth in Indonesia during the period 1975–2024. The research employs a quantitative causal approach using secondary time series data obtained from the World Bank. The analysis is conducted using multiple linear regression with EViews software, supported by stationarity testing (Augmented Dickey-Fuller), Error Correction Model (ECM), and Moving Average (MA) estimation to ensure model robustness in both short-run and long-run dynamics. The results of the study show that investment and exports do not have a statistically significant effect on economic growth. Inflation has a significant negative effect, indicating that higher inflation tends to reduce economic growth, while poverty shows a significant positive relationship with economic growth, suggesting a complex structural condition in the Indonesian economy. Simultaneously, all independent variables jointly have a significant effect on economic growth. The model has an explanatory power of approximately 45.93% (R-squared = 0.4593), indicating that the remaining variation is explained by other factors outside the model. These findings highlight the importance of macroeconomic stability and inclusive development policies in sustaining Indonesia’s long-term economic growth.